Direct and indirect healthcare and carbon savings with ACTIVE Particle ControlTM air-purification - Mark Ereth; Mark Ereth; Judith Fine; Bency Massinello; Heather Gallagher; Eddie Simpser; Frank Stamatatos (Frontiers Media S.A., 2023)
Controlling airborne transmitted disease remains a challenge to clinicians, healthcare administrators, and engineers. Engineering measures are critical to any infection control program but can require extensive installation procedures, may be expensive to maintain, and may not always demonstrate clinical or financial benefit. We determined the financial and carbon benefits of an engineering solution to combat air pollutants and to control airborne transmitted disease. We determined the costs of healthcare associated infections (HAIs), and the costs of installation, maintenance, energy demands, and carbon impacts of an ACTIVE Particle ControlTM (APC) air-purification system. In a 20 month study with over 65,000 patient days the significant reductions in HAIs resulted in significant financial, energy, maintenance, and carbon savings from this engineering solution. Positive clinical and financial outcomes are possible with novel air-purification solutions such as APC.